Developing a Local Wisdom Based Islamic Religious Education Approach to Strengthen Students’ Character in Elementary Schools - Suherni Suherni; Amaluddin Amaluddin; Dadang Sumarna; Amir Patintingan; M. Nasri Hamang (Journal of Education and Learning Sciences, 2026)
This thesis examines: (a) how to design a local wisdom–based Islamic Religious Education (PAI) learning model appropriate for implementation at SD Negeri 129 Bunu, Anggeraja District, Enrekang Regency; (b) how the implementation of the model improves students’ understanding and practice of Islamic values; and (c) how effective the model is in improving learning outcomes and strengthening students’ Islamic character. The objectives of this study are: (a) to develop a PAI learning model design based on local wisdom suitable for school use; (b) to describe its implementation in improving students’ understanding and practice of Islamic values; and (c) to evaluate its effectiveness in learning outcomes and character building. This study uses a descriptive qualitative method with a case study approach conducted for three months at SD Negeri 129 Bunu, Anggeraja District, Enrekang Regency. Primary data sources include the principal, Islamic Education teachers, classroom teachers, and school staff, while secondary data sources include documents, journals, and literature. Data were collected through observation, interviews, and documentation. Data analysis was carried out using data reduction, data display, and conclusion drawing. Data validity was ensured through credibility, transferability, dependability, and confirmability. The findings indicate that the local wisdom–based PAI learning model is effective in improving students’ understanding and practice of Islamic values. The integration of Islamic teachings with local cultural values such as mutual cooperation, respect, sharing, and responsibility makes learning more contextual and meaningful. Students become more active through discussions, group work, and social activities. This approach not only improves cognitive achievement but also strengthens Islamic character, including religiosity, discipline, empathy, and social awareness in both school and community life.